Effects of analgesic and noise stimulus in gait score assessment - De Lima Almeida Paz, Ibiara Correia [UNESP]; De Lima Almeida, Ianê Correia [UNESP]; Milbradt, Elisane Lenita [UNESP]; Caldara, Fabiana Ribeiro; Tse, Marcos Livio Panhoza [UNESP] (My University, 2019)
This experiment was carried out aiming to assess walking manner and speed of broiler chickens with different gait scores (GS), with or without sound stimulus, and with or without administration of analgesic. To that end, 1,000 birds were evaluated by the GS test and 74 were selected for walking speed analyses. Weight at slaughter and breast yield values were obtained for comparisons. Walking speed analyses, both with and without analgesic and with and without stimulus were performed. Non-parametric statistics was applied to the GS data that did not meet the assumptions of the statistical model (normality and homogenicity) using Fisher’s exact test according to the data behavior (P<0.05). The analyses of data on speed, weight at slaughter, and breast yield were evaluated by ANOVA and compared by Tukey’s test (P<0.05). Walking speed differed after acoustic stimulus with or without administration of metamizole sodium. Body weight was also different in each GS. It is thus concluded that the birds may feel discomfort when their GS is higher than 0, but that such discomfort may be suppressed when they are stimulated to walk.